The Fourth Ukrainian-Polish Meeting on Ferroelectricity 15–19 June, 1998, Dnipropetrovsk, Ukraine (Condensed Matter Physics, 1999)
This issue contains Proceedings of the Forth Ukrainian-Polish Meeting on Ferroelectricity held in Dnipropetrovsk 15–19 June, 1998. Such joint international conferences devoted to the problems of phase transitions and ferroelectricity have been carried out by the ukrainian and polish scientists during the last decade.